Indonesian Rheumatology Association Recommendation for Management of Autoimmune Rheumatic Disease Patients During COVID-19 Pandemic - Cesarius Singgih Wahono; Perdana Aditya; Herlina Yani; RM Suryo Anggoro KW; Faisal Parlindungan; Anna Ariane; Andi Raga Ginting; Ika Vemilia; Lisa Kurnia Sari (Indonesian Journal of Rheumatology, 2020)
Background: Coronavirus-19 (COVID-19) disease is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), first reported from Wuhan, the capital of Hubei province, China, in December 2019. Since the occurrence of COVID-19 pandemic, there have been concerns about the risk of SARS-CoV-2 infection and complications in systemic autoimmune-rheumatic patient. Therefore, we intend to make recommendations for the management of autoimmune rheumatic diseases during this pandemic. Method: Indonesian Rheumatology Association (IRA) held an online meeting on May 17th2020 and formed a task force that was in charge to make recommendation for management of adult autoimmune rheumatic disease patients during COVID-19 pandemic. This task force consisted of 9 IRA members that held their first online meeting on May 18th2020. The draft of the recommendation were reviewed in three online meetings that resulted in final recommendation through consensus from all of task force members. The final draft of recommendation was approved by IRA executive board on July 10th2020. Result: The management of autoimmune-rheumatic diseases during the COVID-19 pandemic must consider several important factors such as underlying rheumatic-autoimmune disease factors, risk factors for COVID-19 exposure in autommune-rheumatic disease patients and the presence of COVID-19 infection symptoms Discussion: Recommendations for pharmacological management of autoimmune rheumatic disease patients during COVID-19 pandemic are according to exposure to COVID-19 and the presence of symptoms. There are four groups of patients that are the focus of this recommendation: 1) autoimmune rheumatic disease patients without symptoms of infection AND without risk of exposure to COVID-19; 2)autoimmune rheumatic disease patients without symptoms of infection AND with close contact (exposure) to COVID-19 probable or confirmed patients; 3) autoimmune rheumatic disease patients with symptoms of COVID-19 infection but the infection status is not yet known (suspected and probable case of COVID-19); and 4) autoimmune rheumatic disease patients with confirmed COVID-19 infection. Each groups have different management approaches. Conclusion: Recommendations for the management of autoimmune rheumatic diseases during this pandemic is needed to guide doctors that treat autoimmune rheumatic diseases.